THE POTENTIAL OF IMPLEMENTING INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN SPECIAL INTEREST TOURIST DESTINATION: AN EXPLORATORY STUDY OF INTERNATIONAL TOURISTS OF SUBAK CULTURAL LANDSCAPE IN BALI PROVINCE AS UNESCO’S CULTURAL HERITAGE SITE - Perdhana Dalimunthe, Gallang; Suryana, Yuyus; Kartini, Dwi; Sari, Diana (International Journal of Psychosocial Rehabilitation, 2020)
Tourists can feel the added value of a destination with the application of information and communication technology (ICT), which is currently being promoted by the government and managers of tourist attractions in various countries. Cultural tourism is a tourism segment that is being developed and integrated with ICT. The Subak Cultural Landscape Destination, which is a UNESCO Cultural Heritage located in Bali, is a destination that is visited by many tourists but is not yet equipped by ICTs to add value and provide more experience to tourists. The design method in analyzing ICT devices is needed by tourist destinations, especially the Subak Cultural Landscape, to enrich the destination. Using qualitative methods, open-ended questions can be disseminated to tourists who have visited all cultural landscape destinations. The result is a coding design whose application can be used to determine the ICT tools needed while still promoting the concept of sustainability tourism.